THE TRADITION OF CAROK IN MADURA ACCORDING TO POSITIVE LAW AND ISLAMIC CRIMINAL LAW - Hidayatulloh, Rizki Bagus; Najmudin, Deden; Rozikin, Opik (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Carok is a cultural tradition in Madura, involving a fight or duel using a cerulit knife to restore one's pride and honor that has been trampled on by others. This tradition involves abuse and murder, and the perpetrators are not punished because there is a customary agreement. This is not in accordance with Islamic law and positive law. In Islamic Criminal Law, carok is categorized as a qishash-diyat crime. Meanwhile, according to Indonesian positive law, carok is a criminal act of murder as regulated in Articles 338-340 of the Criminal Code. This study aims to analyze the tradition of carok from the perspective of positive law and Islamic criminal law, including examining the sanctions for perpetrators of carok, the elements and stages of carok, and the customary agreements involved. This study uses a descriptive analysis method with a normative juridical approach. The type of data used in this research is qualitative, using secondary data sources with library research data collection techniques and deductive data analysis techniques. The results of this study show that the tradition of carok violates Positive Law and Islamic Criminal Law. In Islamic Criminal Law, perpetrators are subject to qishash-diyat, and in Positive Law, carok is a criminal act and violates the law. Therefore, carok as a tradition needs to be re-examined.